Stalk-eyed flies carrying a driving X chromosome compensate by increasing fight intensity - Paczolt, Kimberly A.; Pritchard, Macy E.; Welsh, Gabrielle T.; Wilkinson, Gerald S.; Reinhardt, Josephine A. (Frontiers in Ethology, 2024)
Exaggerated ornaments provide opportunities to understand how selection can operate at different levels to shape the evolution of a trait. While these features aid their bearer in attracting mates or fending off competitors, they can also be costly and influenced by the environment and genetic variation. The eyestalks of the stalk-eyed fly, Teleopsis dalmanni, are of interest because eyestalk length is the target of both intra- and intersexual selection and is also reduced by loci on a highly-divergent sex ratio X chromosome (XSR), a meiotic driver accounting for up to 30% of wild X chromosomes. Male stalk-eyed flies fight to control access to females and over food using a combination of low-intensity displays and high-intensity physical fights. We staged, filmed, and scored contests between pairs of eyespan-matched males to evaluate whether X chromosome type impacts the behavior and outcome of aggressive interactions. While our results broadly match expectations from previous studies, we found that XSR males used more high-intensity behaviors than males carrying a non-driving, standard X chromosome (XST), particularly when their eyestalks were of similar size or smaller than their opponents. Additionally, we found that when XSR males use high-intensity behaviors, they win more bouts than when they use low-intensity behaviors. Taken together, these results suggest that XSR impacts male aggressive behavior to compensate for the shorter eyestalks of XSR males and may help to explain how this selfish chromosome is maintained.